Roadway Traffic Analysis Scheme using Unmanned Aerial Vehicle Based on Image Processing and Edge Computing - Abhishek G Athreyasa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Traffic congestion is a major problem which is increasing day by day in developing countries. So, traffic analyzing has become a more important issue. For the development of smart cities, traffic management using UAV is one of the most important asset. UAV used for roadway traffic management are more efficient and easier to detect the traffic and send the required data to the receiver station and it performs continuous operations with no human intervention. There has been voluminous research which provided that unmanned aerial vehicles (UAV’s) are a viable and less time-consuming alternative to real time disturbed traffic analysis and management, providing the eye-in the sky solution to the problem. UAVs use image processing algorithms for detecting the roadways and vehicles. We present a simple approach to road traffic analyzing using UAVs by combining the concepts of edge detection in image processing and edge computing representing the road network. The results reflect the value of flexibility and bird-eye view provided by UAV videos or images thereby depicting the overall applicability of the UAV-based traffic analysis system. The further Research On this application might be done in future.